2003
DOI: 10.1089/153056203772744671
|View full text |Cite
|
Sign up to set email alerts
|

An Economic Analysis of a Store and Forward Teledermatology Consult System

Abstract: Our objective was to assess the economic impact of store-and-forward teledermatology in a United States Department of Veterans Affairs (VA) health care setting. Patients being referred to the Dermatology Consult Service from the Primary Care Clinics at the Durham, North Carolina VA Medical Center were randomized either to usual care or to a teledermatology consultation. Fixed and variable costs for both consult modalities were identified using a microcosting approach. The observed clinical outcomes from the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
1
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(83 citation statements)
references
References 9 publications
3
76
1
3
Order By: Relevance
“…A prior study performed in a VA 12 setting resulted in cost findings contrary to our findings. In that study, store-and-forward teledermatology was the more costly alternative, with the mean cost per participant for teledermatology of $36.40 vs $21.40 for conventional referral from the VA perspective.…”
Section: Discussioncontrasting
confidence: 99%
“…A prior study performed in a VA 12 setting resulted in cost findings contrary to our findings. In that study, store-and-forward teledermatology was the more costly alternative, with the mean cost per participant for teledermatology of $36.40 vs $21.40 for conventional referral from the VA perspective.…”
Section: Discussioncontrasting
confidence: 99%
“…13 Mean waiting intervals reported in studies evaluating TD systems have ranged between 2 and 50 days for TD systems vs the 88 to 137 days demonstrated by the conventional letter referral. 2,[14][15][16] In our series, patients referred to the clinic, one third of whom had malignant lesions, were attended to within the following 2 weeks (mean time, 12.31 days) since they first visited the general practitioner, in accordance with the 2-week rule promoted by health care administrations. 6,7 Along with the faster communication channel that the Internet represents, the avoidance of unnecessary visits to the dermatologist may explain such shortening of waiting intervals.…”
Section: Commentmentioning
confidence: 99%
“…While studies differed in their economic perspective and modality of S&F teledermatology delivery (e.g. triage, consultation, versus provision of care), analyses have generally established that S&F teledermatology offers a cost-effective means of providing dermatologic care especially for those living in geographically isolated communities or medically underserved communities (Pak et al, 2009;Whited et al, 2003). For example, in a cost-minimization analysis that adopted the perspective of the U.S. Department of Defense, Pak et al concluded that the use of teleconsultations through S&F technology reduced overall costs compared to conventional care (Pak et al, 2009).…”
Section: Economic Considerations Of Store-and-forward Teledermatologymentioning
confidence: 99%
“…For example, in a cost-minimization analysis that adopted the perspective of the U.S. Department of Defense, Pak et al concluded that the use of teleconsultations through S&F technology reduced overall costs compared to conventional care (Pak et al, 2009). Similarly, Whited et al performed a cost analysis of a consultative model using S&F technology from the perspective of the U.S. Department of Veterans Affairs (Whited et al, 2003). The authors found that teleconsultations are $15 more costly per patient compared to face-to-face consultation.…”
Section: Economic Considerations Of Store-and-forward Teledermatologymentioning
confidence: 99%
See 1 more Smart Citation